CanWe Identify Macroscopic Texture of Coal under Microscopic Analysis Using Standard Petrographic Method? - Ferian Anggara; Diyan Pamungkas; Wildan Guntur Prakoso (Journal of Applied Geology, 2018)
Macroscopic texture in coals is not much getting attention to identify, becauseit is believed it doesn’t hold much information about the coal characteristics. It is nottrue because some of important coal characteristics lie in its organic content which is reflected in its macroscopic texture (Moore, 2016). Conventional petrographic method using crushed sample cannot distinguish such feature microscopically, since the macroscopic texture will lose its integrity during the preparation. Petrographic analysis using block samples provide information about microscopic texture that can represents its macroscopic texture. Components in textural analysis are divided into three types based on the size, band (more than 800 μm), lens (20–800 μm) and matrix (less than 20 μm). From the ratio between these three types of component and statistics, later it can be determined that nonbandedsamples have less value of ratio between band and lens per matrix, and there will be a borderline between banded and non-banded samples based on the value. Banded texture in macroscopic feature consists of vitrain bands, and under microscope it can beidentified as band and lens of macerals, while non-banded samples will mostly consist ofmatrix texture. Thus, it can be concluded that petrographic analysis using block samplescan be used to identify microscopic texture representing the macroscopic texture, and can be proven through statistics as used in this research.